Сучасні тенденції кібератак та кращі практики для захисту від них - Качан, В. Є.; Нгуєн, Х. Н. (ХНУРЕ, 2022)
This work is devoted to assessing current trends in attacks and best practices to protect against these attacks. The main trends that are not controlled by the security team are considered. Microsoft Security Intelligence Report and SANS (SysAdmin, Audit, Network and Security) Attack Threat Report are used. Common security controls have been identified as the best ways to improve protection.